Quad‐Site Pacing Using a Quadripolar Left Ventricular Pacing Lead. Issue 2 (29th November 2011) - SHETTY, ANOOP K.; MEHTA, PARESH; BOSTOCK, JULIAN; RINALDI, C. ALDO
<x xml:space="preserve">Abstract</x> Pacing the left ventricle (LV) from multiple sites simultaneously may result in a better response to cardiac resynchronization therapy (CRT). We sought to assess whether multisite pacing using a quadripolar LV lead improves acute hemodynamic response (AHR) to CRT. We paced four ventricular sites simultaneously using two vectors of a Quartet lead, a right ventricular apical lead, and an additional LV lead temporarily placed in an anterior branch of the coronary sinus. Multisite pacing using the Quartet lead alone did not improve the AHR but "quad‐site" pacing using an additional temporary LV lead did increase dP/dtmax. (PACE 2013; 36:e48–e50)